Assessing the impact of take-or-pay rates in long-term contracts for hydrogen imports on a decarbonized European energy system under weather variability - Julian Keutz; Jan Hendrik Kopp (Institute of Energy Economics at the University of Cologne (EWI), 2024)
Climate-neutral hydrogen is set to play a crucial role in decarbonizing Europe by 2050. Yet, assumptions on hydrogen imports vary widely across existing studies - ranging from fully flexible to fixed import volumes - often neglecting the modalities of future hydrogen trade such as long-term contracts (LTC). This paper addresses this gap by investigating the implications of Take-or-Pay (TOP) rates in hydrogen LTCs on a decarbonized European energy system. We employ a numerical model that optimizes generation capacity, storage and infrastructure investment, and dispatch decisions for the European power and hydrogen sector in 2050, explicitly incorporating TOP obligations in hydrogen LTCs. Our findings show that varying TOP- rates induce significant shifts in cost-minimal infrastructure requirements of the energy system. These shifts underscore the necessity to account for the degree of import flexibility in planning assessments for future energy systems relying on hydrogen imports. Additionally, we show that reduced import flexibility imposed by high TOP rates is balanced predominantly by increased hydrogen storage and withdrawal capacity while import capacity decreases. By simulating dispatch decisions for 35 weather years for the energy systems planned with representative weather, we find that systems planned with high TOP-rates exhibit a lower reliability when weather characteristics during operation differ from the planning stage.
Keywords: C61; F10; Q27; Q40; Q41; Q48; 330; Energy System Modeling; Hydrogen Infrastructure; Hydrogen Storage; Hydrogen Long-Term-Contracts; Hydrogen and Electricity Markets